Evaluation Of The Rationality Of Antibiotic Use In Hospitalized Adult Patients With UTI Diagnosis On Clinical Outcome At Dr. Moewardi Regional Hospital - Malinda Apriliani; Kharisma Jayak Pratama; Niken Luthfiyanti (CV. AFDIFAL MAJU BERKAH, 2026)
Urinary Tract Infection (UTI) is a common infection with high antibiotic resistance due to irrational use. To assess the rationality of antibiotics in adult inpatients with UTI at Dr. Moewardi Regional General Hospital using the Gyssens method, ATC/DDD patterns, and their relationship with clinical outcomes. A retrospective descriptive observational study of medical records of 50 acute pyelonephritis patients (population 270, Slovin sample e=10%, consecutive sampling), collected in December 2025. LPD medical records; analysis: Gyssens (qualitative Permenkes 28/2021), ATC/DDD (quantitative), Fisher's Exact (p<0.05). 64% female, 52% >60 years; ciprofloxacin 90%; rationality 46% (Gyssens category 0), 54% irrational (mainly short duration 44%); ATC/DDD: ciprofloxacin 47.2%, ceftriaxone 52.8%; outcome improved 94%; p=0.090 (not significant). Rationale was low, especially for duration, with no significant association with outcome; stewardship is recommended to prevent resistance.